The port of Hong Kong : a survey of its development - Chiu, T. N. (Book collections on Project MUSE., 1973)
Hong Kong's one great physical asset is its port. Throughout the one hundred and thirty years of the Colony's history its economy has depended to an important degree on this asset. In this book Dr T. N. Chiu describes and explains the pattern of port development in Hong Kong, where he sees the present structure of port activities as the product of a long period of economic, demographic and political developments.